2021
DOI: 10.1002/mabi.202100134
|View full text |Cite
|
Sign up to set email alerts
|

Robust Electrospun Nanofibers from Chemosynthetic Poly(4‐hydroxybutyrate) as Artificial Dural Substitute

Abstract: Bioresorbable poly(4-hydroxybutyrate) (P4HB) may fulfill the specific requirements that are necessary for a dural substitute, including its high elasticity, long-term strength retention properties, and the biocompatibility without significant accumulation of acidic degradation products. However, commercial P4HB can only be produced by the bacterial fermentation, which limits its applications in the cerebrospinal system due to higher endotoxin restriction. Meanwhile, P4HB can be prepared via the ring-opening po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…For the current study, we produced our own absorbable electrospun P4HB scaffolds. P4HB was chosen as knitted P4HB implants have shown promise in reconstructive surgery for ventral hernia repair and in our preclinical studies for pelvic floor repair. ,,, In addition, electrospun P4HB for other applications such as a dural or dermal , substitution are encouraging, but the available studies are limited, and no studies on electrospun P4HB for pelvic floor repair have been conducted. Because fibroblasts are the main cell type of the connective tissue of the vaginal wall and are responsible for maintaining the ECM, , their function is critical in assessing implant performance in the pelvic floor and to predict how the implant will interact with the host.…”
Section: Discussionmentioning
confidence: 99%
“…For the current study, we produced our own absorbable electrospun P4HB scaffolds. P4HB was chosen as knitted P4HB implants have shown promise in reconstructive surgery for ventral hernia repair and in our preclinical studies for pelvic floor repair. ,,, In addition, electrospun P4HB for other applications such as a dural or dermal , substitution are encouraging, but the available studies are limited, and no studies on electrospun P4HB for pelvic floor repair have been conducted. Because fibroblasts are the main cell type of the connective tissue of the vaginal wall and are responsible for maintaining the ECM, , their function is critical in assessing implant performance in the pelvic floor and to predict how the implant will interact with the host.…”
Section: Discussionmentioning
confidence: 99%
“…We searched the keywords in databases to perform a co-occurrence analysis of dural and materials. Figure 67 porcine model Surgicel/Durasis/DuraGen/Preclude DuraGen dural substitute produced the least amount of inflammation and preclude generated the most, and Durasis demonstrated the least degree of inflammatory cell infiltration of the grafts that were not resorbed Deng et al 68 in vitro decellularized porcine small intestine/ polyester urethane-based Neuro-Patch dural substitute membranes showed cytocompatibility, did not provoke an inflammatory response, and maintained the stemness of hDPSCs better than mineral trioxide aggregate Ma et al 69 in vitro and rats/rabbit model bioresorbable poly(4-hydroxybutyrate) electrospun P4HB membranes have excellent biocompatibility without any foreign body response and the ability to form a continuous neodura tissue similar to native dura mater Huang et al 70 rabbit model photocross-linked hydrogel hydrogel can function as a dural substitute to repair dural defects in rabbits and reduce dural adhesion when compared with the null control Deng et al 51 in vitro and mice model chitin/bacterial cellulose substitutes showed suitable swelling rate and mechanical behavior without cytotoxicity effect, exhibited cell proliferation-promoting properties in vitro, and did not deform in the peritoneal environment of mice with mild tissue inflammation Li et al 42 in vitro and rabbit model fish collagen scaffold scaffold prevented brain tissue adhesion, reduced the possibility of inflammation in rabbit model, and can facilitate the growth of fibroblasts as well as enhance the tissue regeneration Chumnanvej et al 71 rabbit model oxidized regenerated cellulose (ORC)/ poly ε-caprolactone (PCL) knitted fabric composites both samples of rabbit model similarly exhibited biocompatibility and supported the dural regeneration without immunological rejection Sanpakitwattana et al 72 in vitro cefazolin-loaded ORC/PCL bilayered composite composite showed greater densities, but lower thickness, compared to those of drug unloaded composite, and cefazolin released from ORC/PCL bilayered composite was found to be monophasic, comprising mainly a burst release Seo et al 73 porcine model porcine pericardial graft porcine pericardial patch as a dural substitute has efficacy and safety as an alternative graft to use in duraplasty compared with a small intestinal submucosal graft EBC has a more dispersed and regular fiber structure, a better porosity and water holding capacity, and superior degradability compared with common bacterial cellulose; however, the biomechanical properties were slightly decreased Wang et al 75 in vitro nanofibrous substitutes nanofibrous substitutes could provide long-term structural support during the degradation, maintain a sustained release of IGF-1, promote neural cell survival and microenvironment of neurite growth, and play an important role in the neuroprotective effect after injuries Lama et al 49 rat model bacterial cellulose bacterial cellulose membrane showed suitable biocompatibility properties without immune reaction or chronic inflammatory response and neurotoxicity responses…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Due to relatively low market availability, only a few of more than 90 known PHAs are available. In terms of mechanical properties, the most elastic one is P4HB, while PHB is considered to be most rigid [ 111 , 112 ]. There are several papers describing the use of PHAs for soft-tissue replacement.…”
Section: Tissue Engineeringmentioning
confidence: 99%